Enantioconvergent catalysis - Mohr, Justin T.; Moore, Jared T.; Stoltz, Brian M. (Beilstein Journal of Organic Chemistry, 2016)
An enantioconvergent catalytic process has the potential to convert a racemic starting material to a single highly enantioenriched product with a maximum yield of 100%. Three mechanistically distinct approaches to effecting enantioconvergent catalysis are identified, and recent examples of each are highlighted. These processes are compared to related, non-enantioconvergent methods.
Keywords: asymmetric catalysis; enantioselectivity; synthetic methods